Material particulado atmosférico de São Carlos: identificação das fontes de emissões e seus impactos à saúde humana - Carvalho, Jonatas Schadeck (Universidade Federal de São Carlos, 2023)
Air pollution by particulate matter (PM) is one of the main environmental risks to human health. PM has different sizes, emission sources, and a wide range of substances may be present in it. Given this scenario, the objective of this study was to determine the concentration of chemical markers in the MP, identify the sources of emissions and thereby evaluate the potential impacts caused to the environment and health of the population of the city of São Carlos (SP). Given that, 91 samples of PM10 collected between 2015 and 2018 and 86 samples of PM fractionated by size collected between 2019 and 2022 were analyzed. In 5 samples of PM10 and 10 of PM2.5 concentrations were determined higher than the daily limits recommended by the World Health Organization (WHO). The annual limits recommended currently by WHO were also exceeded in 2015, 2016, 2017, 2018, 2020, 2021 (PM10 and PM2,5), e 2022 (PM2,5). The concentrations of PM10, PM2,5, ions, saccharides, PAH, and oxy-PAH showed a seasonal behavior, higher in the dry period. Increasing trends were observed in saccharide, PAH, and nitro-PAH concentrations. These seasonal and temporal behaviors are explained by the increase in fire spots in the state of São Paulo in recent years and because they have a higher incidence in the dry period, in addition to lower wet deposition and greater soil resuspension favored by lower precipitation and relative humidity. These findings are also consistent with the main sources of emissions identified by the positive matrix factoring model: soil resuspension (responsible for 28% of PM10), biogenic emissions (27%), biomass burning (27%), and vehicle emissions together with secondary aerosol (18%). The diagnostic ratios also indicated biomass burning and petrogenic emissions as the main sources of PAH, and the burning of wood and herbaceous plants were the main types of biomass burned. It is noteworthy that the highest concentrations of PAH and nitro-PAH were determined in the PM fraction with the lowest aerodynamic diameter (da), while the highest concentrations of oxy-PAH were determined in coarse PM, probably of biogenic origin. In the fine PM, the oxy-PAH had a secondary origin or by the burning of organic matter. In the PM fraction with larger aerodynamic diameters (da), the determined saccharides were of biogenic origin. In the PM fraction with a smaller diameter, there was a predominance of saccharide emissions from biomass burning. The main sources of ions in the PM were biomass burning, in addition to vehicle and industrial emissions. Other highlights of this work are that approximately 25 to 35 deaths per 100,000 individuals could be avoided annually if the WHO air quality standard (mean annual PM2.5) were not exceeded and that, for the same population, there is a risk of cancer lifetime lung cancer of 1.2 ± 2.5 (PAH concentrations). Therefore, it is concluded that biomass burning is still one of the main sources of air pollution in São Carlos and that PM concentrations, especially in the dry period, are above WHO recommendations, negatively impacting the health of the population.
Particulate matter from São Carlos: source apportionment and health impact assessment
Keywords: Material particulado atmosférico; Fatoração de matriz positiva; Fontes de emissões; Estudo epidemiológico; Atmospheric particulate matter; Positive matrix factorization model; Source apportionment; Epidemiological study; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL